HUBUNGAN DAYA LEDAK OTOT TUNGKAI DAN KOORDINASI MATA TANGAN TERHADAP KEMAMPUAN SHOOTING JUMP SHOOT PADA ATLET BOLA BASKET FAMILY BASKETBALL CLUB PEKANBARU - Kurniawan, Afwan; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to find out among other things the relationship of exlposive muscle power leg and Hand- Eye Coordination of shooting jump shoot capabilities on family basketball basketball club Pekanbaru. An example of this study is the family basketball club Pekanbaru club which is honored by 12 people. Full sampling technique The family basketball team of Pekanbaru who are with 12 people. The result of the violation of the family basketball team Pekanbaru is the first analysis between explosive muscular leg X1 and Y where rtab at a significant level ? (0.05) = r_count (0.9127)> r_tab (0.602), hypothesis meaning and strong relationship between explosive muscular power leg against the ability to shooting jump shoot at the family basketball club Pekanbaru. From the quantitative analysis of both X2 and Y, where r_tab at a significant level ? (0.05) = means r_count (0.948)> r_tab (0.602), the meaning of the hypothesis and the strong relationship between the ability of hand-eye coordination to ability to shooting jump shoot family basketball club Pekanbaru. The third analysis of the relationship of explosive muscle power leg (X1) hand eye coordination (X2) with the results of shooting jump shoot (Y) where rtab at a significant level ? (0.05) = r_count (0.609)> r_tab (0.602), it can be concluded that the relationship between (X1) and (X2) with (Y) or the relationship of explosive muscle power leg and hand-eye coordination with the shooting jump shoot on the strong interpretation.Keywords: Eksplosive Muscule Power, Coordination and Shooting Jump Shoot